Европейское побережье Меотиды (Азовского моря) по Клавдию Птолемею - Зубарев, В. Г. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryZubarev V. G. Europian Coast of Meotida (Azov Sea) According to Claudius PtolemeusThe author on the basis of preliminary analysis of the text «The geographical guide» by Clavdiy Ptolemey made an attempt to specifical localization of stations on the European sea coast of Meotide (Sea of Azov). The character and succession of the description of this region in «The geographical guide» witness the usage at least of 3 sources by Ptolemey, the main of which was periple of Meotic lake from Pantikapey till the mouth of the Tanais (Don). As a result of comparison of coordinate of populated area and geographic names, which were worked out by the author's method, with facts of archaeology and modern geographical state of this region were identified 18 stations from 24 having mentioned by Ptolemy with concrete stations or geographical names. The most part of not exactly identified points is in the archaeological regions, which are insufficiently learnt.